Risk Assessment and Indoor Air Quality - Anderson, Elizabeth L (CRC Press, 2009)
With the recent tightening of air quality standards as mandated by the U.S. EPA, has come great pressure on regulatory bodies at all levels of government, along with the industries and groups affected by these standards, to better assess the hazards and risks that result from air pollutants. Risk Assessment and Indoor Air Quality carefully ties together the tools and methodologies of Risk Assessment to the study of indoor air quality.